Grit and perceived teacher support associations with Chinese language achievement: the mediating role of emotion in Thai high school Chinese classrooms - Pan, Li; Li, Xinyi; He, Xianyue; Luo, Huiqin; Gu, Qizhen (Frontiers in Psychology, 2025)
IntroductionChinese language learning is gaining considerable attention from learners worldwide, leading many countries, including Thailand, to make it a mandatory subject in primary and secondary education. However, many Chinese learners lack interest in learning Chinese, resulting in inadequate Chinese language proficiency. Chinese language learners’ grit and emotional commitment to Chinese language learning are key factors in determining their language learning success, and the support of Chinese as a Foreign Language teachers is also crucial in this process. Thus, this cross-sectional study investigates the associations of students’ grit and perceived teacher support with their Chinese language achievement while considering the potential mediating role of emotions (enjoyment, anxiety, and boredom).MethodsThe study included 665 high school students from two public and three private schools in Bangkok. A questionnaire and an HSK exam paper were the instruments used in this study. Partial least squares structural equation modeling was applied to analyze the data.ResultsThe findings indicated that perceived teacher support, grit, and three emotional factors were each significantly associated with Chinese language achievement. While all three emotions mediated the relationship between perceived teacher support and Chinese language achievement, only foreign language learning enjoyment exerted a mediating role in the association between perseverance and Chinese language achievement.DiscussionWith insights for Chinese language educators and educational administrators, this paper highlights the importance of fostering learning perseverance, supportive learning environments, and meeting students’ emotional needs to improve Chinese language learning achievement.